2021
DOI: 10.3390/horticulturae7080218
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba Seeds—An Environmental Pollutant or a Functional Food

Abstract: Ginkgo biloba has been cultivated in Bulgaria since the end of the 19th century. Ividual specimens can be seen in almost every park. Females of the tree are considered contaminants of the landscape because their ripe seeds have a strong odor and are not utilized. We undertook this study to clarify whether ginkgo seeds of local origin can be converted from an unwanted and unused environmental pollutant into a source of beneficial compounds. Various analytical and chromatographic methods were used to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The approximate calorific value of Ginkgo biloba dried leaves is 287 kcal/g [ 31 ]. In turn, according to the study by Tomowa et al (2021) [ 32 ], the protein content of Ginkgo biloba seeds was 5 g/100 g of raw seeds or about 11 g/100 g dw. The fat content in raw nuts was 1 g/100 g, and in dry matter, 2.04 g/100 g. The content of saturated acids was 19 g/100 g, polyunsaturated 40 g/100 g, and monounsaturated 41 g/100 g. Starch was isolated as seed after extraction with organic solvents and water.…”
Section: Phytoconstituents Of Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…The approximate calorific value of Ginkgo biloba dried leaves is 287 kcal/g [ 31 ]. In turn, according to the study by Tomowa et al (2021) [ 32 ], the protein content of Ginkgo biloba seeds was 5 g/100 g of raw seeds or about 11 g/100 g dw. The fat content in raw nuts was 1 g/100 g, and in dry matter, 2.04 g/100 g. The content of saturated acids was 19 g/100 g, polyunsaturated 40 g/100 g, and monounsaturated 41 g/100 g. Starch was isolated as seed after extraction with organic solvents and water.…”
Section: Phytoconstituents Of Plantmentioning
confidence: 99%
“…It is credited with relieving symptoms, memory functions and handling, dizziness, migraines, or tinnitus. To be able to attribute the pro-health effect of EGb761, it should contain 22–27% of flavonoids and 5–7% of terpenoids and less than 5 ppm ginkgo biloba acid (i.e., 0.0005% ginkgo biloba acid in the preparation) [ 6 , 32 ].…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of converting Ginkgo biloba seeds from an unwanted and unused environmental pollutant into a source of beneficial compounds in Bulgaria was the subject of the article by Tomova et al [10]. The authors applied various analytical and chromatographic methods to quantify the major constituents and ten biologically active compounds in methanol seed extract.…”
Section: Dear Colleaguesmentioning
confidence: 99%
“…Female plants are not desirable for this purpose since their seeds emit a foul odor [ 6 8 ]. Although ginkgo leaf extracts might provide some health benefits, recent studies have revealed that components of ginkgo seed have the potential to cause severe allergic reactions and carcinogenic activities [ 8 12 ]. Amplification of nucleic acid is the most useful method in nucleic acid detection.…”
Section: Introductionmentioning
confidence: 99%